Impact of SARS-CoV-2 pandemic on pancreatic cancer services and treatment pathways: United Kingdom experience. Issue 11 (November 2021) - McKay, Siobhan C.; Pathak, Samir; Wilkin, Richard J.W.; Kamarajah, Sivesh K.; Wigmore, Stephen J.; Rees, Jonathan; Dunne, Declan F.J.; Garcea, Giuseppe; Ahmad, Jawad; de Liguori Carino, Nicola; Sultana, Asma; Silva, Mike; et al.
Abstract: Introduction: The SARS-CoV-2 pandemic presented healthcare providers with an extreme challenge to provide cancer services. The impact upon the diagnostic and treatment capacity to treat pancreatic cancer is unclear. This study aimed to identify national variation in treatment pathways during the pandemic. Methods: A survey was distributed to all United Kingdom pancreatic specialist centres, to assess diagnostic, therapeutic and interventional services availability, and alterations in treatment pathways. A repeating methodology enabled assessment over time as the pandemic evolved. Results: Responses were received from all 29 centres. Over the first six weeks of the pandemic, less than a quarter of centres had normal availability of diagnostic pathways and a fifth of centres had no capacity whatsoever to undertake surgery. As the pandemic progressed services have gradually improved though most centres remain constrained to some degree. One third of centres changed their standard resectable pathway from surgery-first to neoadjuvant chemotherapy. Elderly patients, and those with COPD were less likely to be offered treatment during the pandemic. Conclusion: The COVID-19 pandemic has affected the capacity of the NHS to provide diagnostic and staging investigations for pancreatic cancer. The impact of revised treatment pathways has yet to be realised.